PLAY AND RITUAL – ONTOLOGICAL ASPECTS OF PHOTOGRAPHY - Andra MAVROPOL (Studia Universitatis Babeș-Bolyai. Philosophia, 2017)
Play and Ritual – Ontological Aspects of Photography. This research aims to analyse the ontological aspects of photography that relate to its lack of objectivity, namely the concepts of play and ritual that are important parts in photography’s being in the world. Acknowledging that what appears on the surface of the picture is the result of distortions caused by the technical praxis or by the photographer’s intentional intervention, one should be bound to question photography’s realism. My claim is that the apparently objective picture depicts, in fact, a constructed image that implies a creative process in which the photographer, the model and the spectator are involved. The paper follows Andre Bazin, Jean Baudrillard and Roland Barthes’ discourses about the ontology of photography, through an analysis of its ritualistic aspect, which involves a process of recreating reality through play. The importance of this paper can be highlighted by the fact that it offers an insight into a problem that is often overlooked: the photographic image’s lack of objectivity is rarely questioned on one hand, and on the other, subjectivity can be noticed through the way in which one relates to the photographic image, since it has the ability to depict a person or a scene that can trigger some sort of a personal response to that image in the spectator.